ANALISIS KUALITAS PELAYANAN JASA MENGGUNAKAN METODE SERVQUAL DI BAGIAN PENERIMAAN MAHASISWA BARU INSTITUT INFORMATIKA DAN BISNIS DARMAJAYA BANDAR LAMPUNG - Paramitasari, Niken (Jurnal Manajemen Magister Darmajaya, 2016)
This study aims to determine service quality at Admissions (Bagian Penerimaan Mahasiswa Baru or PMB) of Informatics and Business Institute Darmajaya based on the analysis of five dimensions of service quality in the model SERVQUAL (service quality). Total population is the subject of this study is a new student academic year of 2014/2015 as many as 946 students. The sample consisted of 90 students were selected using sampling techniques such as probability and snow ball technique. Data were analyzed by using a questionnaire form SERVQUAL scale that describes the gaps of service quality expected and perseption of new students IIB Darmajaya then discovered level of satisfaction contained in attributes of servicesconsisting of five SERVQUAL dimensions, tangible, reliabitliy, responsiveness, assurance, and emphaty. The results showed that service quality is not maximized because all the gaps satisfy student is minus or negative. Then analyzed using Cartesian diagram to identify the services based on the level of interest and customer satisfaction for the quality of service in Admissions (PMB). From the results of the integration of SERVQUAL and measurement methods Cartesian diagram, the dominant attributes are in quadrant D, which means that the performance of the organization at a high level but desires or expectations of consumers in the variable is low. Therefore IIB Darmajaya need to maintain the quality of service and strives to improve quality of service to be optimal and placing or moving the attributes that are in the other quadrants, mostly place in quadrant B.Â Keywords â SERVQUAL, Gap Analysis, Cartesian Diagram, Student Satisfaction.